Relevance of Wagner's hypothesis in achieving sustainable development agenda in Nigeria - Isiaq O. Oseni; Ibrahim A. Adekunle (African Governance and Development Institute (AGDI), 2020)
Policy ambiguity in the form of non-directional and non-purposeful use of state resources has made sustainable growth outcomes a mirage in Nigeria. Recent economic crisis prompted the debate on how increased government spending induces sustainable economic growth in Nigeria. This paper examines the validity or otherwise of Wagner's theory in Nigeria for the realisation of the Sustainable Development Goals (SDGs) from 1980 through 2017. Using time-series data on real gross domestic product, total government expenditure, money supply and domestic investment and adopting the two-step Engle and Granger estimation procedure, result shows that increased government spending significantly predicts variations in real gross domestic product and thus leaned empirical credence to Wagner's hypothesis as an essential concept for the attainment of Sustainable Development Goals in Nigeria. This paper recommended that the government should exhaust all possible options to increase expenditure in order to realise sustainable growth in Nigeria.
Keywords: E62; O11; 330; Government Expenditure; Economic Growth; Wagner law and Granger Causality